Quality of Accounting Reporting After the IFRS Adoption in Nigeria (International Journal of Business, Economics and Management, 2016)
This study determined the effect of IFRS on the quality of financial reporting among Nigerian financial firms. The study adopted stock price (Ohlson, 1995) and return (Easton and Harris, 1991) models, that have been commonly used in accounting research. Data were collected from Thompson Reuters (stock price) and Bank Scope Data Streams (net income and total expenses) to determine the relationships. The study found that there is a greater relationship between net income and total expenses with the stock price and return. Furthermore, the relationships have been statistically significant using Cramer Z-statistic for both stock price and return model. The overal result have shown value relevance of net income, operating expenses, and change in net income and operating expenses has improved as a result of IFRS adoption among Nigerian listed financial institutions. The study implication for the policy makers, standard setters and investors are to give more emphasis on the use of IFRS for all firms even if they are not listed in the stock market as IFRS adoption provided a better quality accounting information than domestic reporting. Besides the relevance of these study findings to security market, the literature has provided greater contributions to fewer market research in African capital market particularly, Nigeria after the IFRS adoption being the first study to carry such study in Nigeria.